Researching our own practice: an experience of self-supervision - Silva, Raquel (2020)
In this article a self-supervision experience developed by a pre-primary teacher is presented. Resorting to video recordings made in the activities classroom, this teacher observes and reflects on her practice and then she audio-records her reflections in dialogue with a critical friend, consolidating this formative experience with a collaborative work.  Using an action-research methodology, the pedagogical content knowledge and the reflection/ questioning dimensions were selected to analyze the collected data, in order to identify strategies that promote the self-supervision of practices.  The results showed that self and hetero-observation and critical analysis of the educational choices made in action by this pre-primary teacher and discussed later with a critical friend, with whom she shares experiences, promote changes in educational practices, contributing for teacher professional knowledge and development.